"What Is Security?" Conference with Keynote Speaker Richard Lehman - Watkins, Howard::::::::: (1987)
Workshop panel; Carolyn Carter speaker; others ?, Hon. Armando Rodriguez and Dorothy Smith; portable cassette recorder on table